2000
DOI: 10.1046/j.1365-2389.2000.00339.x
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved components in precipitation water percolated through forest litter

Abstract: Leaves lying on the forest¯oor are a major source of dissolved organic substances in soil and surface waters, and these substances have important effects in those environments. We used zero-tension lysimeters to study the chemical characteristics of water percolating through litter from various species of forest trees. The leaching rates were greatest in the autumn and declined rapidly thereafter, especially for deciduous litter. During an annual cycle, 2.5±17% of the initial contents of the carbon in the litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
52
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 25 publications
(18 reference statements)
4
52
1
Order By: Relevance
“…20 mL of sample was added to each flask. Aqueous samples with more than 10 mg C L À1 were diluted before incubation to avoid overgrowth of microorganisms (Hongve et al, 2000) and to minimise concentration effects on DOM biodegradation (Zsolnay, 2003). Nutrients (equal weights of NH 4 NO 3 and K 2 HPO 4 ) were added in order to adjust the C:N ratio to about 10:1 and facilitate DOM biodegradation (McDowell et al, 2006).…”
Section: Doc Biodegradationmentioning
confidence: 99%
“…20 mL of sample was added to each flask. Aqueous samples with more than 10 mg C L À1 were diluted before incubation to avoid overgrowth of microorganisms (Hongve et al, 2000) and to minimise concentration effects on DOM biodegradation (Zsolnay, 2003). Nutrients (equal weights of NH 4 NO 3 and K 2 HPO 4 ) were added in order to adjust the C:N ratio to about 10:1 and facilitate DOM biodegradation (McDowell et al, 2006).…”
Section: Doc Biodegradationmentioning
confidence: 99%
“…First, a decrease in the pH values of soils after the application of acidic forest litter resulted in an intensive desorption of copper into soil solution [9,18]. Secondly, released copper was bound by low molecular weight organic acids (formed as a result of litter decomposition in biochemical processes) and transformed into the complexed forms [4,6,19] Fig. 3) in the lasts days of incubation.…”
Section: Resultsmentioning
confidence: 99%
“…Such a treatment may, however, create hazards associated with an increase of copper solubility in afforested areas caused by the influence of organic matter that derives from forest litter. Copper has a high affinity to organic matter [1][2][3] and can be complexed by low molecular weight organic acids produced from decomposing litter [4][5][6]. Moreover, microbiological decomposition of litter leads to acidification of the soil environment, which may directly contribute to enhanced desorption of copper into soil solution.…”
Section: Introductionmentioning
confidence: 99%
“…Doerr et al (1998) did a similar experiment with leachates of pine needles and found an increase of soil hydrophobicity in the treated soils. Hongve et al (2000) found that percolates from deciduous and coniferous litter contained large fractions of hydrophobic compounds, with coniferous litter having the greatest concentrations. These experiments with pine leachates are in agreement with findings of soil water repellency in unburned pine forests (Richardson and Hole, 1978;Scott, 2000;Doerr et al, 2009).…”
mentioning
confidence: 99%